Paleoenvironmental evidence for first human colonization of the eastern Caribbean. (1st December 2015) - Siegel, Peter E.; Jones, John G.; Pearsall, Deborah M.; Dunning, Nicholas P.; Farrell, Pat; Duncan, Neil A.; Curtis, Jason H.; Singh, Sushant K.
Abstract: Identifying and dating first human colonization of new places is challenging, especially when group sizes were small and material traces of their occupations were ephemeral. Generating reliable reconstructions of human colonization patterns from intact archaeological sites may be difficult to impossible given post-depositional taphonomic processes and in cases of island and coastal locations the inundation of landscapes resulting from post-Pleistocene sea-level rise. Paleoenvironmental reconstruction is proving to be a more reliable method of identifying small-scale human colonization events than archaeological data alone. We demonstrate the method through a sediment-coring project across the Lesser Antilles and southern Caribbean. Paleoenvironmental data were collected informing on the timing of multiple island-colonization events and land-use histories spanning the full range of human occupations in the Caribbean, from the initial forays into the islands through the arrival and eventual domination of the landscapes and indigenous people by Europeans. In some areas, our data complement archaeological, paleoecological, and historical findings from the Lesser Antilles and in others amplify understanding of colonization history. Here, we highlight data relating to the timing and process of initial colonization in the eastern Caribbean. In particular, paleoenvironmental data from Trinidad, Grenada, Martinique, and Marie-Galante (Guadeloupe) provide a basis for revisiting initial colonization models of the Caribbean. We conclude that archaeological programs addressing human occupations dating to the early to mid-Holocene, especially in dynamic coastal settings, should systematically incorporate paleoenvironmental investigations. Highlights: Evidence for first humans in the eastern Caribbean date to c. 5000 cal yr BP. Proxies include pollen, phytoliths, soil chemistry, and charcoal particles. Through multiproxy analysis natural vs. anthropogenic landscapes are distinguished. First occupants followed a stepping-stone strategy of island colonization.